2014
DOI: 10.1371/journal.ppat.1003886
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of Trypanosoma brucei Cell Cycle Progression and Differentiation Identified Using a Kinome-Wide RNAi Screen

Abstract: The African trypanosome, Trypanosoma brucei, maintains an integral link between cell cycle regulation and differentiation during its intricate life cycle. Whilst extensive changes in phosphorylation have been documented between the mammalian bloodstream form and the insect procyclic form, relatively little is known about the parasite's protein kinases (PKs) involved in the control of cellular proliferation and differentiation. To address this, a T. brucei kinome-wide RNAi cell line library was generated, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
261
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(278 citation statements)
references
References 52 publications
14
261
0
3
Order By: Relevance
“…Tb927.11.8150 is a member of the ubiquitous Unc-51-like kinase 4 (ULK4) family, and we refer to it as FCP5/TbULK4. The T. brucei genome contains a second gene coding for an ULK protein, Tb927.11.4470, a member of the Fused family (24). This FCP6/TbFused protein tagged with YFP was also found to localize specifically to the new flagellum tip of dividing cells (SI Appendix, Fig.…”
Section: Structure Immunoprecipitation Approach Identifies Flagellummentioning
confidence: 99%
“…Tb927.11.8150 is a member of the ubiquitous Unc-51-like kinase 4 (ULK4) family, and we refer to it as FCP5/TbULK4. The T. brucei genome contains a second gene coding for an ULK protein, Tb927.11.4470, a member of the Fused family (24). This FCP6/TbFused protein tagged with YFP was also found to localize specifically to the new flagellum tip of dividing cells (SI Appendix, Fig.…”
Section: Structure Immunoprecipitation Approach Identifies Flagellummentioning
confidence: 99%
“…For example, the protozoan parasite must have genes that function to control the cell cycle to ensure correct coordination of multiplication. In the case of T. brucei, the molecular components of cell cycle control are well characterized (31). At least 45 genes, mostly encoding protein kinases, have been identified that are essential for parasite growth and replication.…”
Section: Possibilities For Using Single-cell Protozoans As Model Systmentioning
confidence: 99%
“…However, it must be recognized that a coevolutionary journey between host and parasite should ensure no death of the host, upon which it depends, before finding their way to a new host. Despite the dependence of a protozoan parasite on the host, the innate cellular mechanisms, such as control of the cell cycle and differentiation, are analogous in protozoan, metazoan, or human cells (31). Failure of these processes (uncontrolled parasite growth and incorrect differentiation) could lead to further adverse pathogenesis to the host caused by an increased parasite load, causing cell and tissue destruction-a similar outcome to that generated by invasive cancer cells.…”
Section: Possibilities For Using Single-cell Protozoans As Model Systmentioning
confidence: 99%
“…DNA replication initiator factor. Associates with GINS and MCM complexes, and travels with the replication fork DDK (CDC7/DBF4) CDC7 CDC7 Not found (Jones et al, 2014;Parsons et al, 2005;Tiengwe et al, 2012a) Catalytic subunit of DDK (CDC7/DBF4), required for origin firing and replication fork progression in mitotic S phase DBF4 DBF4 Not found (Tiengwe et al, 2012a) Regulatory subunit of DDK (CDC7/DBF4), required for origin firing and replication fork progression in mitotic S phase TICRR (Treslin) SLD3 Not found (Dang & Li, 2011;Genois et al, 2014;Li, 2012) Genes nomenclature has been retrieved from HUGO gene nomenclature committee (http://www.genenames.org/) for H. sapiens; SGD: Saccharomyces genome database (http://www.yeastgenome.org/) for S. cerevisiae; and GeneDB (http://www.genedb.org). For Leishmania, genes names designation follows the guidelines for Trypanosoma and Leishmania genetic nomenclature (Clayton et al, 1998).…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 99%
“…This could be explained by extensive sequence divergence. Indeed, several kinases involved in replication have been described in trypanosomatids (Jones et al, 2014;Parsons et al, 2005). It is possible that one or more of these kinases is the functional homolog of CDC7.…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 99%